LEGAL STANDING APPOINTED STATE CIVIL APPARATUS IN REPLACEMENT THE HEAD REGION OF REGION AUTONOMY POST CONSTITUTIONAL COURT VERDICT NO. 67/PUU-XIX/2021 APRIL 20, 2021 - Tuanaya, Halimah Humayrah (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2022)
Appointed State Civil Apparatus (SCA) as replacement ended time of Head Region in year 2022 and 2023, for the Governor, Head Regent, Mayor, basicly those are pragmatic side made by the Central Government to accommodate several aspect. The discretion legitimate the appointment in range of moment until the new Head Region elected in gather election 2024. Meanwhile, the appointment potentially would causing new disputes and could be the SCA shall not focus on the on progress several program region government. Therefore, the appointment philosophically did not parallel in the spirit of democracy and region autonomy because of centralistic controlling not decentralistic system.